ANALISIS KINERJA INVESTASI EMAS DAN SAHAM PT ANEKA TAMBANG MENGGUNAKAN PENDEKATAN SHARPE RATIO PERIODE 2020–2025 - Satriani, Nilla; Rayyani, Wa Ode; Fuada, Nurul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the return and risk levels, as well as investment performance based on the Sharpe ratio, between ANTAM gold bullion and ANTM shares for the 2020-2025 period. The study uses a quantitative descriptive approach with secondary data in the form of monthly closing prices of ANTAM gold, ANTM share prices, and the BI Rate as a proxy for the risk-free rate. The analytical methods used include calculating returns, standard deviations, and the Sharpe ratio. The results show that ANTAM gold has a consistent positive return pattern during the crisis period with a moderate risk level and a downward trend. Meanwhile, ANTM shares exhibit high volatility with very high returns only in 2020 and 2025. From 2022 to 2024, ANTM shares experienced prolonged pressure due to a global commodity oversupply and rising interest rates. Based on the Sharpe ratio, ANTAM gold recorded positive values in five of the six observation years, with a peak efficiency of 3,921 in 2025. Meanwhile, ANTM shares only achieved positive values in 2020 (1,325) and 2025 (1,832). Gold's ability to maintain a positive Sharpe ratio across nearly all periods makes it superior as a long-term investment instrument that prioritizes value stability. ANTM shares can be an option for aggressive investors willing to endure high volatility and able to understand global commodity cycles. The combination of the two instruments is considered strategic for creating a balance between risk and return in portfolio management.